PERSEPSI MASYARAKAT MADURA TERHADAP PENGGUNAAN FINANCIAL TECHNOLOGY (FINTECH) DAN FINANCIAL TECHNOLOGY SYARIAH - Atik Emilia Sula; Merie Satya Angraini (Ulumuna: Jurnal Studi Keilsman, 2022)
This study aims to photograph and explore the perception of the Madurese community towards the use of financial technology (Fintech) and sharia financial technology. The study in this research is related to the development of an inclusive society, where the fintech theme is currently overgrowing in its use by the community along with technological developments in the 4.0 revolution era. Fintech combines the financial system with technology to become an innovation that facilitates the financial system. Informants in this study were Madurese from four districts, namely Bangkalan, Sampang, Pamekasan, and Sumenep, both using or not using fintech services. Data collection techniques used questionnaires and in-depth interviews with informants with various backgrounds, ages, genders, and professions. The analysis technique used is a qualitative descriptive method with a phenomenological approach that is useful for providing facts and data accurately. Keywords: Madura Community Perception, Fintech, Sharia Fintech.